Data Byte: An Insight on Fetal Alcohol Spectrum Disorder and Educational Achievement - Piatt, Carley; Lamba, Navjot; Jia, Ruiting; Werk, Christine (International Journal of Population Data Science, 2018)
Introduction Data Bytes are bite-sized pieces of data from the longitudinal project, Experiences of Alberta Children and Youth Over Time, 2005-06 to 2010-11. To promote public engagement, the Data Byte series is designed to highlight a finding from a full report to give readers a quick data morsel to chew on. Objectives and Approach Fetal Alcohol Spectrum Disorder (FASD) is a complex disorder caused by alcohol exposure during pregnancy. To understand how young people with FASD in Alberta are performing in schools, individually linked administrative data were used from 2005/06 to 2010/11. An individual was considered to have FASD if, at any point in the 6 years, they received a diagnostic code for fetal alcohol syndrome, or for being newborn affected by maternal use of alcohol (ICD 10-CA Q86.0 or P04.3) from a health service (emergency department or ambulatory care visit, or a hospitalization), or from a child disability service program. Results Of young Albertans with FASD, almost 40% were meeting or exceeding educational expectations compared to 80% of young Albertans without a diagnosis of FASD. Expectations for educational achievement were computed by Alberta Education using age, grade, school type, special education codes, provincial achievement test scores, home education status, number of high school credits earned, number of higher level courses taken, average grade in higher level courses, possession of an Alberta Education certificate or diploma, and Alexander Rutherford scholarship eligibility. Conclusion/Implications Data Bytes are designed to encourage stakeholders to explore: Is the definition of “meeting educational expectations” used for the general population appropriate for a population with complex needs? What other outcomes might be used to determine whether services are improving the quality of life for young Albertans with FASD?